Comparison of iatrogenic articular cartilage injury in canine stifle arthroscopy versus medial parapatellar mini‐arthrotomy in a cadaveric model. (14th November 2017) - Rogatko, Cleo P.; Warnock, Jennifer J.; Bobe, Gerd; Verpaalen, Valentine D.
Abstract: Objective: To assess iatrogenic articular cartilage injury (IACI) resulting from arthroscopy versus medial parapatellar mini‐arthrotomy of the stifle. Study design: Paired comparison of canine cadaver stifles treated with arthroscopy or mini‐arthrotomy Animals: Paired canine stifles from 14 cadavers (≥20 kg). Methods: Stifles (N = 28) were assigned to arthroscopy or arthrotomy. Full stifle joint exploration and meniscal probing were performed. Joints were disarticulated and India ink assay performed. IACI was defined as sharply delineated lesions with India ink uptake. Incidence, number, and lesion area in defects articular cartilage, incision length, surgery duration, and joint structures visualized were recorded. Results: Arthroscopy resulted in greater IACI than mini‐arthrotomy, including incidence of IACI (arthroscopy: 13 stifles, mini‐arthrotomy: 4 stifles; P = .009), number of IACI per stifle (arthroscopy: 3.4 ± 2.90, mini‐arthrotomy: 0.9 ± 1.96; P = .04), and IACI area (arthroscopy: 5.9 ± 7.58 mm 2, mini‐arthrotomy: 1.7 ± 4.50 mm 2 ; P = .003). Incision length was shorter with arthroscopy (1.0 ± 0.38 cm) versus mini‐arthrotomy (5.3 ± 0.61 cm; P < .0001). Surgical duration was not significantly different between groups (arthroscopy: 12.5 ± 3.49 minutes, mini‐arthrotomy: 11.05 ± 1.60 minutes; P = .21). Visualization of articular structures was incomplete in 14/14 mini‐arthrotomy stifles and 1/14 arthroscopy stifles ( P < .001). Conclusion: Incidence, number, and area of IACI were greater in the arthroscopy group versus the mini‐arthrotomy group. Mini‐arthrotomy resulted in a longer incision and incomplete joint visualization. Methods of preventing IACI and clinical significance of IACI warrant further investigation.